PERANCANGAN WHEEL TURBINE PADA PEMBANGKIT LISTRIK MIKRO GAS TURBIN - Eko Prasetyo Prasetyo; Rudi Hermawan Hermawan; Muhammad Edza Fakhri; Rini Prasetyani Prasetyani; Erlanda Augupta Pane (Jurnal Ilmiah Teknik Mesin POROS, 2021)
Micro gas turbine power generator has advantages in low maintenance and operational costand can be moved easily. Gas fueled micro gas turbine generate power by delivering pressurizedcombustion gas to mechanical power and stored in battery via altenator. In this research, turbine whellfrom Garrett TA31 in micro gas turbine is redesigned to increase the system performance. Experiment ofredesigned turbine wheel is then compared with the previous configuration turbine wheel performance.The results show the system power is increased from 0,23 kW to 3,1 kW.